A Legal-Historical Study of Legal Institutions and Special Autonomy Policy in Papua - Diana Gloria Wamafma; Juanda Nawawi; Nurlinah; Hashim Balas; Saleem Asouli (PT. Islamic Research Publiser, 2026)
This study examines how the historical trajectory of Otsus and the evolution of its legal-institutional framework—particularly the roles of the Governor, the Regional People's Representative Council of Papua and Regency/City Councils (DPRP/DPRK), and the Papuan People's Assembly (Majelis Rakyat Papua/MRP)—have shaped the direction of legal politics concerning meaningful participation, affirmative representation for OAP, special fiscal arrangements, and the agenda of historical clarification and human rights protection. This research employs normative (doctrinal) legal methods with a legal-historical specification. It utilizes statutory, historical, and conceptual approaches, complemented where relevant by a limited case approach. Primary legal materials include Law No. 21 of 2001 and its subsequent amendments, particularly Law No. 2 of 2021, as well as key implementing regulations. Secondary materials consist of recent scholarly literature on Papua’s special autonomy framework. The analysis is conducted through regulatory inventory, historical periodization, before-and-after mapping of key legal norms, institutional analysis, and vertical and horizontal legal synchronization. The findings indicate that: (i) Otsus incorporates explicit mandates concerning OAP recognition, human rights protection, public participation, and the institutional role of the MRP; however, implementation and evaluation have often prioritized fiscal transfers and development programs without adequately addressing deficits of political legitimacy and unresolved human rights concerns; (ii) initiatives aimed at strengthening governance through village-oriented development and the provision of basic public services have not fully resolved accountability challenges; and (iii) several revisions introduced under the second phase of Special Autonomy (Otsus II) are perceived to diminish the significance of local-cultural representation in strategic decision-making processes and to weaken mechanisms for meaningful participation. This article contributes a legal-historical analytical framework that bridges critiques of existing law (ius constitutum) with reform-oriented perspectives (ius constituendum), thereby supporting more substantive participation, a strengthened role for the MRP, and a more credible accountability framework within Papua’s special autonomy governance.